Development Of Module Teaching Materials With Predict - Oberve - Explain (POE) Models Based On Gamification On Triangle Materials - Nurhaliza Nurhaliza; Laila Maharani; Rizki Wahyu Yunian Putra (Department of Mathematics Education University of Muhammadiyah Malang, 2019)
The learning process is certainly not only limited to the increase in students' knowledge or cognitive abilities, but also includes better behavior and thinking abilities, and no less important is how the learning process makes students able to solve problems faced both in learning in school, as well as in the daily life they experience. The development of ICT technology has had an impact on the development of the games industry, which makes educators more creative in designing their learning processes. Some game designers have studied deeper about psychology or other sciences that study human motivation and behavior. The method in this research is research and development (R&D) with the ADDIE development model. Data collection instruments used were questionnaires given to material experts and media experts to find out the feasibility of the product, and given to students and educators, to find out the attractiveness of the products that have been developed as well as pretest and posttest test instruments. Based on the analysis of data obtained from material experts and media experts, it was stated that the teaching materials developed were feasible to be used, and the analysis of the data obtained from students and educators stated that the teaching materials developed were very interesting. The results of the analysis of the effectiveness of class data applied teaching material obtained and calculated with the formula Effect Size obtained is . E_s calculation results are then interpreted to see the effectiveness criteria, the magnitude of , which is in the range of , based on the category determined by the level of effectiveness of the magnitude of the class applied to learning using module teaching materials with the Predict - Oberve learning model - Explain (POE) based on gamification on the material of SMP triangles is categorized quite effective with a classification classified as medium.